Strategic Policy Framework for Sustainable Geopark Development Aimed at Advancing Village Independence within the UNESCO Global Geopark GunungSewu Region - Nugraha, Rizki Praba; Fauzi, ⁠Akhmad; Rustiadi, Ernan; Basuni, Sambas (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2026)
Indonesia’s diverse cultural, natural, and geological resources boost tourism. Geoparks are key to sustainable development, and the Gunung Sewu Geopark is recognized by UNESCO. However, its main use in tourism does not yet fully affect the village's independence. This study addresses research gaps by proposing an integrated policy framework that uses multi-criteria analysis to consider economic, social, and environmental factors as an effort to improve village selfsufficiency and governance geopark. Using the multi-criteria policy analysis (MULTIPOL) method, this research examines the alignment among the priorities of scenarios, policies, and action plans. The findings reveal that priority scenarios in Gunung Kidul and Wonogiri enhance GSUGGp community advantages by increasing community awareness (CpcityBhav), with the highest average values of 17.4 and 17, respectively. In Pacitan, two priority scenarios are identified: strengthening regulations and institutions for sustainable GSUGGp management (InstituReg) and CpcityBhav, both with average value of 16.8. Policy and action plan priorities across the three regencies show that Gunung Kidul and Pacitan focus on marketing and boosting tourism activities to stimulate local economies, while Wonogiri emphasizes community-based initiatives through tourism and local entrepreneurship. At the program level, regional differences emerge in priority actions, including partnerships, green investments, education-based tourism, and university collaboration. This study highlights the importance of locally adaptive, integrated policies to overcome institutional fragmentation and promote sustainable Geopark development that strengthens village independence. The strategic framework developed offers practical relevance for geoparks facing similar cross-jurisdictional challenges.